Effect of Sr-substitution on the structural and magnetoelectric properties of Ni-Zn ferrites (Bangladesh Journal of Physics, 2020)
Spinel type polycrystalline Ni0.6-xZn0.4SrxFe2O4 (x = 0.0, 0.05, 0.10, 0.15 and 0.20) ferrites are synthesized by solid state reaction method. X-ray diffraction (XRD) pattern reveals the formation of spinel structure with two secondary phases Sr2FeO4 and SrFe12O19 for higher concentration of Sr (0.15 and 0.20). An increase in lattice constant is observed with the increase of Sr content in the lattice. The density of the samples is found to decrease whereas porosity increases with the substitution of Sr2+ ions. Microstructural investigation shows that the grain size increases with the increase of Sr content. Magnetic hysteresis is investigated at room temperature. All the samples exhibit lower coercivity values indicating that the materials belong to the class of soft ferrites. The saturation magnetization is found to decrease with Sr content which is attributed to Néel’s two sub-lattice model of ferrites. The real permeability of the samples remains almost constant up to a certain frequency and then falls rapidly. Improved dielectric constant is observed in the Sr2+ substituted samples. The electrical conduction in these ferrites is explained on the basis of hopping mechanism between the Fe2+ and Fe3+ ions.Bangladesh Journal of Physics, 26(2), 1-20, December 2019